Imunoexpressão de metaloproteinases 2 e 14 e do inibidor TIMP-2 no câncer colorretal - Furtado, Francisco Nélson Nóbrega (2012)
FURTADO, Francisco Nélson Nóbrega. Imunoexpressão de metaloproteinases 2 e 14 e do inibidor TIMP-2 no câncer colorretal. 2012. 88 f. Dissertação (Mestrado em Patologia) - Universidade Federal do Ceará. Faculdade de Medicina, Fortaleza, 2012. === Submitted by denise santos (denise.santos@ufc.br) on 2012-11-01T14:12:20Z No. of bitstreams: 1 2012_dis_fnnfurtado.pdf: 3539375 bytes, checksum: 6fa044d4558e54c9cf489e3b99de3a10 (MD5) === Approved for entry into archive by Erika Fernandes(erikaleitefernandes@gmail.com) on 2012-11-06T13:53:21Z (GMT) No. of bitstreams: 1 2012_dis_fnnfurtado.pdf: 3539375 bytes, checksum: 6fa044d4558e54c9cf489e3b99de3a10 (MD5) === Made available in DSpace on 2012-11-06T13:53:21Z (GMT). No. of bitstreams: 1 2012_dis_fnnfurtado.pdf: 3539375 bytes, checksum: 6fa044d4558e54c9cf489e3b99de3a10 (MD5) Previous issue date: 2012 === The colorectal cancer (RCC) is highly prevalent in richer and industrialized countries. The matrix metalloproteinases (MMPs) are regarded as important for facilitating tumor invasion and spread in various cancers, including colorectal. Tissue inhibitors of metalloproteinases (TIMPs) are the major physiological inhibitors of MMPs. The expression of metalloproteinase-2 (MMP-2), metalloproteinase 14 (MMP-14) and tissue inhibitor of metalloproteinases-2 ( TIMP-2) in colorectal cancer was assessed. CD68 immunostaininig was utilized to the characterization of mononuclear cells nature. Paraffin-embedded tissues from patients undergoing colectomy for colorectal cancer in the period 2004 to 2010, were selected from the files of the Department of Pathology and Forensic Medicine (DPML), Medical School , Federal University of Ceará (UFC). Tissue microarrays were performed and slides were obtained for immunohistochemical detection of the expression of MMP-2, MMP-14 and TIMP-2 and the tissue samples analyzed. The following scores were applied: 0 = no immunostaining or rare labeled cells (<5%), 1 = slight marking the majority (> 50%) of tumor cells or stromal mononuclear cells, or moderate marking in a minority of cells (<50%) 2 = moderate labeling in the majority (> 50%) of tumor or mononuclear cells or intense marking in the minority of cells (<50%) and 3 = intense labeling in the majority (> 50%) of tumor cells or mononuclear cells. In this study, the relationship between increased expression of MMP-14 in mononuclear primary tumor cells and cases without lymph node metastases (MMP-14, 2 and 3/N0 scores: 23/26 = 88%; N1-N3: 14/21 = 67%, p = 0.0353) was stablished . However, no significant relationship was found between the immunohistochemical expression of MMP-14, MMP-2 and TIMP-2 in primary tumors in cancer cells and mononuclear cells and other clinico-pathological parameters. The expression of MMP-2 were negative in the neoplastic cells both in primary tumors (47/47 = 100%) and in metastatic ones (12/12 = 100%). The immunoreactivity of MMP-14 in neoplastic cells in primary tumors was positive (50/50 = 100%) and in all cases except one of metastatic carcinoma (7/8 = 88%). In mononuclear cells, most of them characterized as macrophages (CD68 stained), MMP-14 positive expression also predominated markedly, both in primary tumors (46/47 = 98%) and in metastatic carcinomas (9/10 = 90%). TIMP-2 expression in neoplastic cells of primary tumors occurred in 35/50 cases (70%) and lymph nodes showed positive immunostaining in all cases (8/8 = 100%). In both sites there were no cases with high expression. The TIMP-2 immunoreactivity in tumour associated macrophages (TAMs) was even higher than in the neoplastic cells. In conclusion, MMP-14 and TIMP-2 are frequently expressed in colorectal carcinomas in both anatomical sites , mainly in lymph node metastasis, suggesting that these proteases play an important role in local invasion and tumor progression of these cancers. The predominance of these biomarkers in mononuclear cells, clearly evident in the positivity for MMP-2, emphasizes the importance of tumor microenvironment in the development of neoplasms. === O câncer colorretal(CCR) é altamente prevalente nos países mais ricos e industrializados. As metaloproteinases de matriz (MMPs) são importantes enzimas que facilitam a invasão e disseminação do tumor em vários tipos de câncer, inclusive o colorretal. Os inibidores teciduais de metaloproteinases (TIMPs) são os principais inativadores fisiológicos destas enzimas. Este estudo avaliou a expressão de metaloproteinase-2 (MMP-2), metaloproteinase-14 (MMP-14) e inibidor tecidual de metaloproteinases-2 (TIMP-2) no câncer colorretal. O imunomarcador CD68 foi utilizado para caracterizar a natureza das células mononucleadas do estroma. Amostras teciduais de 50 casos de colectomias, devido ao câncer colorretal no período de 2004 a 2010, obtidas dos arquivos do Departamento de Patologia e Medicina Legal (DPML), Faculdade de Medicina da Universidade Federal do Ceará (UFC), foram analisadas. Realizou-se tissue microarrays e a seguir imuno-histoquímica para avaliar a expressão de MMP-2, MMP-14 e TIMP-2 de acordo com os seguintes escores baseados em outros relatos: 0= sem imunomarcação ou raras células marcadas (<5%); 1 = discreta marcação na maioria (> 50%) das células tumorais ou células mononucleares do estroma, ou moderada marcação em uma minoria de células (<50 %); 2 =marcação moderada na maioria (> 50%) de células tumorais ou células mononucleares ou intensa marcação em minoria de células (<50%); 3 = marcação intensa na maioria (> 50%) de células tumorais ou células mononucleares. Observou-se relação entre a expressão aumentada de MMP-14 em mononucleares de tumor primário e casos sem metástases linfonodais (MMP-14, escores 2 e 3/N0 : 23/24 = 95%; N1-N3: 14/20 = 70%, p = 0,0353). No entanto, nenhuma relação significativa foi encontrada entre a expressão de MMP-14, MMP-2 e TIMP-2 nos tumores primários em células cancerosas ou mononucleares e outros parâmetros clínico-patológicos. A imunoexpressão de MMP-2 foi negativa nas células neoplásicas, em tumores primários (47/47=100%) e metastáticos (12/12 = 100%). A imunorreatividade de MMP-14 em células neoplásicas foi frequentemente positiva em tumores primários (50/50 = 100%) e metastáticos (7/8= 88%). Em mononucleares, a maioria dos quais macrófagos (corados pelo CD68), a expressão positiva de MMP-14 também predominou marcadamente, tanto em tumores primários (46/47 = 98%) como em carcinomas metastáticos (9/10 = 90%). A expressão de TIMP-2 em células neoplásicas, discreta, ocorreu em 70% de tumores primários (35/50 casos) e 100% dos metastáticos (8/8). A imunocoloração para TIMP-2 em macrófagos associados ao tumor (TAMs) foi ainda mais elevada do que nas células neoplásicas. Em conclusão, a MMP-14 e TIMP-2 são frequentemente expressas em carcinomas colo-retais em ambas localizações anatômicas, principalmente nas metástases para linfonodos , sugerindo que estas proteases desempenham papel importante na invasão local e na progressão tumoral neste tipo de câncer. A predominância destes marcadores nas células mononucleares (sobretudo macrófagos) , claramente evidentes na positividade para a MMP-2, enfatiza a importância do microambiente tumoral no desenvolvimento de neoplasias.